EFEKTIVITAS PELAYANAN PROGRAM KELUARGA HARAPAN BAGI KELUARGA PENERIMA MANFAAT DI DESA MOJOREJO KECAMATAN JETIS KABUPATEN PONOROGO - Susilowati, Naomi; Oktariyanda, Trenda Aktiva (Universitas Negeri Surabaya, 2023)
Program Keluarga Harapan (PKH) services are one of the services in the national social assistance program that has been implemented in Mojorejo Village since 2007. PKH services in Mojorejo Village are carried out by a Social Facilitator. The purpose of this study is to describe the effectiveness of PKH services for Beneficiary Families in Mojorejo Village, Jetis District, Ponorogo Regency. However, in this PKH service, there are problems that challenge PKH Social Facilitator. These problems are related to the difficulty of changing the mindset of PKH Beneficiary Families (KPM) Mojorejo Village to become more productive and independent. The method used in this research is descriptive qualitative method. While the theory used is the theory of program effectiveness according to Annas (in Bastaman, 2020: 177) which includes seven indicators, namely timeliness, human resources who manage the program, work mechanisms, cooperation and communication, correct distribution of funds, no deviations, and monitoring and evaluation. The results showed that PKH services for Beneficiary Families in Mojorejo Village were quite effective. This is because of the seven effectiveness indicators used, four of them have been carried out optimally. The four indicators are timeliness, human resources who manage the program, cooperation and communication, and monitoring and evaluation. Meanwhile, three indicators, namely the work mechanism, the correct distribution of funds and no deviations, still have obstacles that cause these three indicators to be less than optimal.